2012
DOI: 10.1371/journal.pone.0039731
|View full text |Cite
|
Sign up to set email alerts
|

Non-Stationarity in the “Resting Brain’s” Modular Architecture

Abstract: Task-free functional magnetic resonance imaging (TF-fMRI) has great potential for advancing the understanding and treatment of neurologic illness. However, as with all measures of neural activity, variability is a hallmark of intrinsic connectivity networks (ICNs) identified by TF-fMRI. This variability has hampered efforts to define a robust metric of connectivity suitable as a biomarker for neurologic illness. We hypothesized that some of this variability rather than representing noise in the measurement pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
373
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(387 citation statements)
references
References 47 publications
13
373
0
1
Order By: Relevance
“…may be a more sensitive marker for mental conditions than metrics about stable characteristics of the brain (16). Preliminary research has already revealed differences in dwell time between controls and both Alzheimer's disease patients (42) and schizophrenics (43). In two recent reviews on resting state dynamics (4,16), it was acknowledged that a better understanding of the relationship between BOLD dynamics and behavior was still needed.…”
Section: Discussionmentioning
confidence: 99%
“…may be a more sensitive marker for mental conditions than metrics about stable characteristics of the brain (16). Preliminary research has already revealed differences in dwell time between controls and both Alzheimer's disease patients (42) and schizophrenics (43). In two recent reviews on resting state dynamics (4,16), it was acknowledged that a better understanding of the relationship between BOLD dynamics and behavior was still needed.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are an important reminder that the typical measures of connectivity isolated in this literature capture only the most robust effects leaving unknown transient shifts in network connectivity. By modeling stochasticity in time series data (e.g., via sliding time windows) one can determine the timing and variability of observable connections to better understand how neural networks adapt to challenge and disruption (Gates & Molenaar, 2012;Hillary et al, 2011a;Jones et al, 2012;Kiviniemi et al, 2011;Leonardi et al, 2013).…”
Section: Discussion Primary Findingsmentioning
confidence: 99%
“…Some studies have reported that 30 s of data suffices to discriminate between cognitive states and to estimate reliable modular graph metrics (Jones et al, 2012;Shirer et al, 2012). We therefore chose a sliding window length of 30 TRs to capture changes in FC over time.…”
Section: Timescales and Potential Confounds Of Dynamic Fcmentioning
confidence: 99%